Body size reduction in mammals; how are the teeth getting along? : An investigation of dog and wolf molars potentiality to shed light on insular dwarfing and the origins of hominin island forms - Sandell, Mia (Helsingin yliopisto, 2023)
Evolution can lead to changes in body size among mammals and when that occurs, organs usually scale along. Teeth are an organ that scale along with body size and therefore, investigating how the teeth are getting along when a mammal is subjected to a rapid reduction of body size is of value. During human evolution, body size has generally increased but jaw and teeth size has decreased. As of recent, human evolution witness a potential decrease of body size, due to the discovery of island-living hominins; Homo floresiensis and Homo luzonensis. The phenomenon of decreasing body size among large animals and increasing body size among small animals in an insular setting is so well-known that it has its own ecological rule, called the island rule or Foster’s rule. However, this phenomenon has not really been studied from the perspective of teeth. In this thesis I focus on the effects of body size decrease on teeth in the context of relatively rapid body size reduction. Researching the effect that a reduction of body size has on teeth is relevant for understanding morphological changes related to island dwarfism and the origins of island forms among humans. Dogs (Canis familiaris) provide an extreme example of rapid and large reduction of both body- and teeth size. Comparing dog molars to molars of their closest ancestor, the wolf (Canis lupus), can shed light on how the teeth behave when scaling down in size. This reduction in body size may be comparable to insular dwarfing as selective breeding of pure breed dogs is limiting the availability of mating partners in a similar way that a secluded island limits the availability of mating partners for insular animals. To answer my research questions, I measure and photograph dog molars and compare the results with data of wolf molars. Furthermore, if any patterns emerge, data of human molar is compared to the canid data to investigate if any similarities can be found. The results show that dog molars are overall smaller in size than wolf molars and that both species ...